Carcinoma of the lung and diffuse interstitial pulmonary fibrosis. Issue 4 (July 1968) - Fox, B.; Risdon, R. A.
Abstract : The clinical and histopathological findings are presented in two cases of diffuse interstitial pulmonary fibrosis in which carcinoma of the lung developed. In one case with rheumatoid arthritis and diffuse interstitial pulmonary fibrosis there was `malignant pulmonary adenomatosis', an association which does not appear to have been reported before. In the second case idiopathic diffuse interstitial pulmonary fibrosis was complicated by large cell anaplastic carcinoma of the lung. It is suggested that in both cases the development of carcinoma of the lung was a complication of the epithelial hyperplasia and scarring that occurs in diffuse interstitial pulmonary fibrosis. It is also suggested that carcinoma found in the main bronchi in patients with diffuse interstitial pulmonary fibrosis should not be regarded as coincidental unless careful search has excluded a carcinomatous change in the periphery of the scarred lungs.